Probabilities and seat gains of minor parties in the 2019 municipal legislative election in Surabaya City, Indonesia - Muhdi, Muhdi; Marijan, Kacung; Aribowo, Aribowo; Fauzi, Mohammad; Hanik, Umi (Masyarakat, Kebudayaan dan Politik, 2024)
This study examines the relationship between seat acquisition probabilities and the acquisition of minor party seats in the 2019 Surabaya City DPRD election. This research is crucial because theoretically the proportional representation electoral system quota/allocation of electoral district seats (dapil) has the probability to be accessed by all parties participating in the election, but in fact in the 2019 Surabaya City DPRD election the quota/allocation of seats was dominated by large parties. This research method is library research with the analysis technique using the Pearson Product Moment statistical test. According to the research results, first, the relationship between seat acquisition probability and minor party seat acquisition is negative and insignificant. The results of the research hypothesis test show rcount (-0.753) < rtable (0.997). Second, the relationship between these two variables controlled by the threshold variable is significantly positive. The research hypothesis test result is rcount (0.000) > rtable (0.997). Based on this research: (1) the electoral system of proportional representation quota/allocation of electoral district seats is not accessible to all minor parties participating in the election; (2) the size of electoral districts with seat quotas in the medium-large criteria does not have a significant positive effect on the acquisition of seats of parties participating in the election; (3) the threshold simultaneously affects the significant positive relationship between the size of the medium-large quota electoral districts and the acquisition of seats of parties participating in the election; and (4) the acquisition of party votes below the lower threshold still has the probability to get the remaining seats.